Respuesta :

Answer:

D

Step-by-step explanation:

We are given the two functions:

[tex]f(x) = 5x^2-x+1 \text{ and } g(x) = -3x[/tex]

And we want to find:

[tex](f \circ g)(1)[/tex]

Recall that this is equivalent to:

[tex]=f(g(1))[/tex]

Evaluate g(1):

[tex]g(1) = -3(1) = -3[/tex]

Substitute:

[tex]=f(-3)[/tex]

Evaluate f(-3):

[tex]f(-3)=5(-3)^2-(-3)+1=49[/tex]

Therefore:

[tex](f \circ g)(1) =49[/tex]

Our answer is D.

Answer:

49

Step-by-step explanation:

ƒ(x) = 5x2 – x + 1 and g(x) = –3x

(ƒ ∘ g)(1)

First find g(1) = -3(1) = -3

Then find f(g(1) = f(-3)

f(-3) = 5(-3)^2 - (-3) +1 = 5(9) +3+1 = 45+4 = 49